2023
DOI: 10.1002/jmv.28787
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network based prediction of the lung tissue involvement as an independent in‐hospital mortality and mechanical ventilation risk factor in COVID‐19

Miłosz Parczewski,
Jakub Kufel,
Bogusz Aksak‐Wąs
et al.

Abstract: Introduction: During COVID-19 pandemic, artificial neural network (ANN) systems have been providing aid for clinical decisions. However, to achieve optimal results, these models should link multiple clinical data points to simple models. This study aimed to model the in-hospital mortality and mechanical ventilation risk using a two step approach combining clinical variables and ANN-analyzed lung inflammation data.Methods: A data set of 4317 COVID-19 hospitalized patients, including 266 patients requiring mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Other individuals had cold feeling and dysfunction of gustation or olfaction which were possibly temporary side effects of the immune response to vaccination 24 , 25 . Studies have shown that using artificial intelligence to interpret radiological findings provides high sensitivity and specificity for the diagnosis of COVID-19 as well as predicting severity 26 , 27 . Although currently, COVID-19 infection is no longer as serious as in previous periods the disease still appears seasonally in Vietnam as well as many other countries around the world.…”
Section: Discussionmentioning
confidence: 99%
“…Other individuals had cold feeling and dysfunction of gustation or olfaction which were possibly temporary side effects of the immune response to vaccination 24 , 25 . Studies have shown that using artificial intelligence to interpret radiological findings provides high sensitivity and specificity for the diagnosis of COVID-19 as well as predicting severity 26 , 27 . Although currently, COVID-19 infection is no longer as serious as in previous periods the disease still appears seasonally in Vietnam as well as many other countries around the world.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence (AI) is a popular topic in radiology such as for rapid disease (e.g., COVID-19) detection on various platforms including mobile devices [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Additionally, the number of AI research articles in radiology has grown exponentially over recent years [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%